Colonic involvement in Stevens-Johnson syndrome. Issue 968 (5th June 2006) - Powell, N; Munro, J M; Rowbotham, D
Abstract : Severe gastrointestinal tract involvement is a rare manifestation of Stevens-Johnson syndrome (SJS). The case is described of a 17 year old man who developed SJS secondary to phenytoin. In addition to the cutaneous, ocular, and oral mucosal lesions typical of SJS, he also developed persistent, bloody diarrhoea associated with life threatening malnutrition. Serial colonoscopy showed severe and progressive colitis. He was treated with a combination of long term nutritional support, probiotic therapy, and supportive measures. He was eventually discharged from hospital six months after admission when the diarrhoea improved and he began to gain weight.